Pages of history of dance culture in Tuva - Biche-ool, Vladimir K. (The New Research of Tuva, 2012)
History of formation, development and a current state of the Tuva dance is considered in the article. The creative characteristic is given to the ballet masters, teachers, those actors who have devoted their lives to the Tuvan dance.
Keywords: art; dance; Tuva; ethnicity; dance culture